Bearing technology across the data center based on SDN - Hanjiang LIU; Liang OU; Wenhua CHEN; Hong TANG (Dianxin kexue)
The development of the internet industry and the rise of cloud computing have created requirements on interconnectivity across data center，and software defined network technology provides important means to solve the network bottleneck problem of data center interconnectivity.Firstly，several commonly used interconnectivity technologies across data center were introduced，and advantages of SDN technology were analyzed.Then，the operator solution of data center interconnectivity bearing technologies based on SDN was put forward，and implementation ideas of this solution were explained.It is a solution which can realize network virtualization across data center，and provide kinds of business functions，such as service customization of user，automatic accessing of network，isolation strategy between different virtual machine，traffic scheduling，the nearest access of user，disaster recovery and backup across data center.